Lion & Lamb - Patterson, James, 1947-; Swierczynski, Duane (Little, Brown and Company, 2023)
"Philadelphia is in a state of shock over the fate of two hometown heroes: Eagles starting quarterback Archie Hughes, and his even more famous wife, Grammy-winning singer Francine Hughes. One spouse is murdered. The other is suspect #1. Even before the case hits the courtroom, it's the hottest ticket in town. For the defense: Cooper Lamb, private investigator to the stars. For the prosecution: Veena Lion, a sleuth so bright she's got to wear shades. Between them, they know every secret in Philadelphia. Together, they prove how two wrongs can make a right. They are Lion & Lamb"--
Includes an excerpt for 12 Months to Live (pages 3-15 at end of work).
Keywords: Private investigators -- Fiction; Murder -- Investigation -- Fiction; Football players -- Fiction; Women singers -- Fiction; Philadelphia (Pa.) -- Fiction; Thrillers (Fiction); Novels; Detective and mystery fiction